Potočka zijavka. Fertility Rites in The Raining CavePotočka zijavka. Obredja plodnosti v Deževni jami - Odar, Boštjan (Studia mythologica Slavica, 2012)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Potočka zijavka is one of the most mysterious Palaeolithic cave sites in Europe. For the first time it is proposed that in this cave 32-36 thousand years ago fertility rites were performed, worshipping a cave bear as totemic animal. Interestingly, we will not find any other archaeological traces in the cave, not even from the youngest historical periods, except of a rock-bowl that was hand-carved with chisel. Though there is no reliable information about the origin and meaning of the rock-bowl, another Slovenian cave site offers a very intriguing explanation about an old Slovene faith and fertility rite. At least in the Late Middle Ages the fertility rite was abandoned in Potočka zijavka, but the cave itself continued to play an important role in Christian religious thought as a sacred place until the 20th Century. The most exciting is the idea about the interplay of three basic elements, important for life: earth, water and sun. Thus we can follow the concept of trinity most probably far back into Palaeolithic times.